Subchondral fracture of the femoral head in children: Differential diagnosis of pediatric hip pain - Ryosuke Yamaguchi; Tomoyuki Nakamura; Takuaki Yamamoto; Kazuyuki Takamura; Haruhisa Yanagida; Toru Yamaguchi; Yasuharu Nakashima (Journal of Orthopaedic Surgery, 2020)
This report describes clinical and radiographic characteristics of two pediatric patients with a presumptive diagnosis of subchondral fracture of the femoral head made based on their clinical course and imaging findings. An 8-year-old boy and an 8-year-old girl had subchondral fracture in the femoral head without osteonecrosis, which was verified by contrast-enhanced magnetic resonance imaging. Although complete disappearance of the fracture line was confirmed in the boy, the girl had a residual femoral head deformity after conservative treatment. Subchondral fracture of the femoral head should be included in the differential diagnosis of pediatric hip pain.